ЕВРОПА И ДРУГАТА ЕВРОПА НА ЕВРОПСКАТА ФЕСТИВАЛСКА ТЕАТАРСКА СЦЕНА (Philological Studies, 2019)
The focus of this study is the play-script Hotel Europa by Goran Stefanovski (2000), which the author created especially for a multimedia theatre event staged and co-produced by Intercult Stockholm, The Avignon Festival, Wiener-Festwohen, Bonner Biennale and The Bologna Festival. The theatre project was directed by nine Eastern European directors and more than twenty-five actors, stemming from various Balkan and Baltic states, countries which at the beginning of the 21st century were not a part of the European Schengen community. This play-script by Stefanovski follows the thematic paradigm set by two of his previous scripts, namely Casabalkan (1996), Euralien (1998) – a project that was created in collaboration with thirteen directors and fifty actors, as part of the festivities surrounding Stockholm’s presiding as a European culture capital), but also in other playbills from the same time period, such as: Ex YU (1996), We are all People (1998), etc. In fact, the underlying idea of all these texts, which in turn ask of us to reconsider the internal borders of Europe, is further examined by Stefanovski in his collection of essays Stories from the Wild East (2005). The focus of the script Hotel Europa, populated by the otherwise silenced voices and languages of the peoples and cultures on the other side of the border (the Schengen border), are the cultural stereotypes which the playgoers face about the perception of the Other, generated as such by the positionality of the borders. The topos of the Balkans, as Another Europe, is presented in the script through the wider context of the always seemingly newly established European internal borders and differences: 1.) the ideologically-political, between the East and the West (in regards to the Berlin Wall and its Fall); 2.) the culturally-traditional; 3.) the economical. The concept of a standing audience, accompanying an array of characters and dramatic situations depicted in the imaginary topos found on the verge between Europe and the (an)Other Europe – a kind of a refugee camp found on Europe’s dooryard – marks the mutual demonization in the perception of Europe’s Other. The series of dramatic situations in the numerous niches (chamber spaces) of “The Hotel Europa” marks the symptoms of the trauma which accompanies the trend/prerogative for the integration of the European identity/identities. On the other hand, Stefanovski’s script, as an integral part of the aforementioned international theatre project, like the rest of Stefanovski’s projects realized in this shared pragmatic context, can also be viewed as a particularly telling contribution (intention) to have the voices/languages of the Other Europe heard, thus pointing out, ever so loudly, their exclusion from the numerous theatre festivals of united Europe (as for example, Europe’s theatrical Oscar – Europe Theatre Prize, especially its New Theatrical Realities programme).